Bringing back the lost monument: interactive virtual model of Sompur Mahavihara, Bengal - Rashid, Md. Mizanur; Rahaman, Hafizur (2008)
This study aims at developing an interactive virtual model of the lost architectural heritage of the 8th century Buddhist Monastery of Sompur Mahaviahara in Bengal. This monument at Paharpur drew the attention of the architectural historians of the South Asia from the very discovery of the ruins of the structure at the beginning of the twentieth century because of its unique architectural features and strategic spatio-temporal location. Several attempts have been made so far to recover the memories of this medieval Buddhist Monastery after the amnesia of a millennium. However, the limited amount of archaeological resource, literary evidences and epigraphic records at the disposal of the architectural historians appears as the main thicket. This study is an attempt to generate an interactive virtual model of the monument that would accommodate different contesting narratives regarding its architecture. It looks into the history in a more dynamic way and uses virtual reconstruction as flexible tool to reconstruct the lost form of the building. The main idea is to develop a method conserving, retrieving and commemorating the both tangible and intangible aspects of the heritage through the participation of the general public. This model will be used as a virtual museum for continuous and feedback and verification from scholars and aspiring general public and eventually refine the model based on these feedback. This participatory approach of reconstructing will minimize the distance between the people and object of heritage as well as engender a new way of experiencing, evaluating and appreciating heritage buildings.